A method for the design of a continuous microalgae culture photobioreactor in series with recirculation system - Vargas, Sandra; Gómez- Pérez, César- Augusto; Espinosa, Jairo (CT&F - Ciencia, Tecnología y Futuro, 2017)
Nowadays, there are functional pilot scale PhotoBioReactors (PBRs), which present serious challenges when performing a scaling up process for an industrial application. The aim of this research was to evaluate the design of several continuous flat plate PBRs connected in series, while allowing constant circulation from the last to the first unit. Scaling up feasibility using the adjunction of new units, instead of PBRs volume increase is analyzed. An ad hoc mathematical model based on mass balances and constitutive equations from literature was constructed; the model integrates the illumination and mass transfer effects on microalgae growth kinetics by a complete model solution. Unfortunately, the model is too complex to be analyzed by conventional methods. Furthermore, it presents problems when evaluated by numeric methods as the results do not have physical meaning and the initial condition has strong effect on the final solution. Hence, this paper presents a simple method to analyze the design of this kind of continuous system. The method allows the design parameters calculation of PBRs system resulting physically in a simple way without having to guess possible system solutions. Moreover it is also shown that the continuous PBRs in series with a recirculation system obtain good amount of microalgae productivity.